2020
DOI: 10.2991/jrnal.k.200222.002
|View full text |Cite
|
Sign up to set email alerts
|

Approaching AI and Robotics in an Eco-friendly Way

Abstract: Merging among them the most important open questions of the century, in this paper, we outline and define a wide range of possible applications and technical forms of a low-energy dissipation in robotic biotechnological system conceived for intelligent and playful interactions. Moving from earlier works on Wearable and Modular Robotics, we describe how, by using modular robotics for creating wearable, it is possible to obtain an approximatively self-sustainable and flexible wearable system, consisting of freel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Nordic countries have a deep-rooted culture of environmental research, with a wide diversified scientific production on ecotechnologies. Authors from these countries have focused on various topics, which include the recycling of carbon and nutrients from domestic and industrial wastewater [ 28 ]; the conversion of organic waste into several products, such as electricity, biodiesel, and organic fertilizer [ 29 ]; the development of more environmentally friendly production technologies to curb the negative environmental impacts of salmon aquaculture [ 30 ], and even the use of artificial intelligence and robotics in eco-technological projects [ 31 ]. The experience of these countries in integrating renewable energy sources into different sectors, particularly wind generation in the electricity market, is remarkable [ 32 ].…”
Section: Countries’ Production Vs Specialization: a Multidimensional ...mentioning
confidence: 99%
“…Nordic countries have a deep-rooted culture of environmental research, with a wide diversified scientific production on ecotechnologies. Authors from these countries have focused on various topics, which include the recycling of carbon and nutrients from domestic and industrial wastewater [ 28 ]; the conversion of organic waste into several products, such as electricity, biodiesel, and organic fertilizer [ 29 ]; the development of more environmentally friendly production technologies to curb the negative environmental impacts of salmon aquaculture [ 30 ], and even the use of artificial intelligence and robotics in eco-technological projects [ 31 ]. The experience of these countries in integrating renewable energy sources into different sectors, particularly wind generation in the electricity market, is remarkable [ 32 ].…”
Section: Countries’ Production Vs Specialization: a Multidimensional ...mentioning
confidence: 99%
“…Tavana Amlashi et al (2021) demonstrated that AI allows creating environmentally friendly practical solutions for the production sector. Pagliarini and Lund (2020) developed and introduced an eco-friendly approach to artificial intelligence and robotics.…”
Section: Introductionmentioning
confidence: 99%